PDGF-B Gene Therapy Accelerates Bone Engineering and Oral Implant Osseointegration - Chang, Po-Chun (2009)
Platelet-derived growth factor-BB (PDGF-BB) stimulates repair of healing-impaired chronic wounds such as diabetic ulcers and periodontal lesions. However, limitations in predictability of tissue regeneration occur due in part to transient growth factor bioavailability in vivo. Here, we report that gene delivery of PDGF-B stimulates repair of oral implant extraction socket defects. Alveolar ridge defects were created in rats and were treated at the time of titanium implant installation with a collagen matrix containing an adenoviral (Ad) vector encoding PDGF-B (5.5×10(8) or 5.5×10(9) pfu/ml), Ad encoding luciferase (Ad-Luc; 5.5×10(9) pfu/ml; control) or recombinant human PDGF-BB protein (rhPDGF-BB, 0.3 mg/ml). Bone repair and osseointegration were measured via backscattered SEM, histomorphometry, microcomputed tomography, and biomechanical assessments. Further, a panel of local and systemic safety assessments was performed. Results demonstrated bone repair was accelerated by Ad-PDGF-B and rhPDGF-BB delivery compared to Ad-Luc, with the high dose of Ad-PDGF-B more effective than the low dose. No significant dissemination of the vector construct or alteration of systemic parameters was noted. In summary, gene delivery of Ad-PDGF-B demonstrates regenerative and safety capabilities for bone tissue engineering and osseointegration in alveolar bone defects comparable to rhPDGF-BB protein delivery in vivo.